2016
DOI: 10.1371/journal.pone.0156561
|View full text |Cite
|
Sign up to set email alerts
|

Hypothetical Rectal Microbicide Acceptability and Factors Influencing It among Men Who Have Sex with Men in Tianjin, China

Abstract: ObjectivesTo measure potential acceptability of rectal microbicides and to explore factors likely to affect their acceptability among men who have sex with men (MSM).MethodsCross-sectional and retrospective surveys were conducted in this study. A questionnaire and a scale were used to measure the acceptability score for physical and functional characteristics of hypothetical rectal microbicides. We also evaluated the involvement of other factors such as sexual behaviors, social context, etc.ResultsMSMs we inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Both of these studies demonstrated very high rates of recent lubricant use, similar to those found in the USA, and higher than those reported among men who have sex with men in Indonesia and Lima, Peru (Carballo-Diéguez et al 2000; Morineau et al 2011; Clark et al 2013; Thienkrua et al 2016; Zhang et al 2016). …”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Both of these studies demonstrated very high rates of recent lubricant use, similar to those found in the USA, and higher than those reported among men who have sex with men in Indonesia and Lima, Peru (Carballo-Diéguez et al 2000; Morineau et al 2011; Clark et al 2013; Thienkrua et al 2016; Zhang et al 2016). …”
Section: Introductionsupporting
confidence: 64%
“…Some recent work has been conducted in Asian countries that examined associations between consistent lubricant use, condom use, and other factors among men who have sex with men in Bangkok, Thailand (Thienkrua et al 2016) and willingness to use lubricants and recent lubricant and condom use among men who have sex with men in Tianjin, China (Zhang et al 2016). Both of these studies demonstrated very high rates of recent lubricant use, similar to those found in the USA, and higher than those reported among men who have sex with men in Indonesia and Lima, Peru (Carballo-Diéguez et al 2000; Morineau et al 2011; Clark et al 2013; Thienkrua et al 2016; Zhang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Designing & developing suppository formulations for anti-HIV drug delivery Review among the 'men who have sex with men' (MSM) community was reported, suggesting that rectal microbicides have a potential market in the MSM population and may have an important role in HIV/STI prevention [29,60]. Since the real challenge to ART suppositories may be social rather than pharmacological, further studies may be considered to combine clinical acceptability studies with clinical research together to understand the true feelings and perceptions of the MSM population when they use the products [29,30,61,62].…”
Section: Current Suppository Formulation Strategies For Antiviral Drug Deliverymentioning
confidence: 99%